Emerging evidence that the ban on asbestos use is reducing the occurrence of pleural mesothelioma in Sweden - Järvholm, Bengt (Scand J Public Health, 2015)
Aims: Several countries have banned the use of asbestos. The future health impacts of previous use have been modeled but there are to our knowledge no convincing studies showing a decreased occurrence of asbestos-related diseases due to a ban. The aim of our study was to estimate the effects of the ban and other measures to decrease the use of asbestos in Sweden. Methods: The effect was measured through comparing the incidence of pleural malignant mesothelioma in birth cohorts who started to work before and after the decrease in the use of asbestos, i.e. in mid-1970s. Cases were identified through the Swedish Cancer Registry and the analysis was restricted to persons born in Sweden. Results: Men and women born 1955–79 had a decreased risk of malignant pleural mesothelioma compared to men and women born 1940–49 (RR 0.16, 95% CI 0.11–0.25; and RR 0.47, 95% CI 0.23–0.97 respectively). The decreased use of asbestos prevented each year about 10 cases in men and two cases in women below the age of 57 years in 2012. Conclusions: The ban and decreased use of asbestos in Sweden can be measured today in birth cohorts that started their working career after the decrease.